Sistem Pakar Dalam Mendiagnosis Penyakit Leishmaniasis Menerapkan Metode Case-Based Reasoning (CBR) - Asyahri Hadi Nasyuha; Yohanni Syahra; Moch Iswan Perangin-Angin; Dedi Rahman Habibie; Aloysius Agus Subagyo (Universitas Budi Darma, 2023)
Leishmaniasis caused by protozoa of the genus Leishmania, is one of the neglected zoonoses. Sand flies (mosquitoes) of the genus Phlebotomus transmit Leishmaniasis. Leishmaniasis has attacked 98 countries and is widespread in tropical, subtropical and Mediterranean regions. Because it primarily affects endemic areas in developing countries, which often have dense populations, malnutrition, poor sanitation, and a lack of human resources for disease control, prevention, and treatment, leishmaniasis is considered a neglected tropical disease. Leishmaniasis is one of the neglected tropical diseases, it is based on the low level of public awareness and scarcity of funds for research to develop effective disease control methods. Leishmaniasis is a difficult condition to treat because the general public is not well aware of it. Based on these problems, an expert system for the diagnosis of leishmaniasis was studied. An expert system is a program that can simulate the thought process of a computer expert and solve problems that are usually handled by experts. Knowledge stored in expert systems is often obtained from human subject matter experts. By using the help of expert systems and calculations carried out using the Case-Based Reasoning (CBR) approach, this study aims to facilitate the diagnosis of Leishmaniasis based on the patient's perceived input. Approach (CBR) can facilitate diagnosis then produce more precise diagnostic results. The test results with the Case-Based Reasoning approach found that the type of disease Cutaneous Leishmaniasis had the highest similarity value with a similarity value of 73%.